Polytrauma dan Injury Severity Score (ISS) - Gigaramadan Sema; Helmi Ismunandar; Rani Himayani; Risti Graharti (Medula, 2023)
Polytrauma is trauma that occurs at several areas on the body, followed by decline in physiological function which has the potential to cause multiple organ dysfunction and death in patients. Initial assessment of polytrauma is important to identify injuries that require initial treatment, determine the management of these injuries, and assess the patient's prognosis. There are several scoring systems that can be used to assess polytrauma injuries. Abbreviated Injury Scale (AIS) can be used to assess the severity of the injury and the probability of death of the patient. The Injury Severity Score (ISS) is a scoring system that assesses the three most severe injuries from six body regions. New Injury Severity Score (NISS) is an update from ISS; assessment of the three most severe injuries to the body regardless of body region. These assessment methods can help the trauma care system to better prevent complications and death in polytrauma patients.